How to write fast under pressure - Vassallo, Philip 1953- (New York American Management Association, 2010)
Anyone who regularly deals with work-related writing deadlines knows the kind of paralysis that can take over when there's too much to accomplish and not enough time to compose a clear sentence. This book contains an usable approach based on the mnemonic DASH, standing for the four critical components needed by writers, working under pressure.
DASH : getting to the task -- Direction : hitting the ground running -- Acceleration : writing on the fly -- Strength : standing fast in the midst of chaos -- Health : planning for the unexpected -- DASH : keeping a fresh approach.
Electronic reproduction.
Keywords: Business writing; Authorship; Electronic books